On the Function of Saccharides during the Nucleation of Calcium Carbonate–Protein Biocomposites - Duchstein, Patrick; Kniep, Ruediger; Zahn, Dirk (Crystal Growth & Design, 2013)
The molecular mechanism of calcium carbonate nucleation in the presence of various types of collageneous proteins is unravelled from computer simulation of ion-by-ion association steps. Single calcium ions are incorporated in the triplehelix by formation of salt bridges to carbonyl and hydroxyl groups of collagen, while single carbonate ions tend to bind laterally to the biomolecule. However, upon multiple ion association, the self-organization of the forming aggregate strongly depends on the triple-helical collagenous strand. In absence of glycosylated lysine residues, we observed that carbonate ions bind to calcium ions that are already incorporated into the triple helix and eventually cause the unfolding of the protein. On the other hand, otolin-1, a specific, collagen-like protein found in biogenic calcite-based composites such as otoconia, comprises a particularly high degree of glycosylated amino acids which avoid such ``destructive'' calcium–carbonate contacts by providing alternative association sites more lateral to the backbone. This leads to the formation of a saccharide–calcium carbonate agglomerate that does not compromise the protein's triple helix and constitutes the organic–inorganic interface of the nucleating biocomposite.
EAM Import::2019-03-08